Synopsis purioris theologiae = Synopsis of a purer theology - Velde, Roelf T. te; Faber, Riemer A.; Ferwerda, R. (Rein); Asselt, Willem J. van (Willem Jan van), 1946-; Boer, William den (Studies in medieval and Reformation traditions ;, 2015)
This bilingual edition of the Synopsis Purioris Theologiae (1625) makes available for the first time to English readers a seminal treatise of Reformed Scholasticism. Composed by four professors of Leiden University (Johannes Polyander, Andreas Rivetus, Antonius Walaeus, and Anthonius Thysius), it gives an exhaustive yet concise presentation of Reformed theology as it was conceived in the first decades of the seventeenth century. From a decidedly Reformed perspective, the Christian doctrine is defined in contrast with alternative or opposite views (Catholic, Spiritualist, Arminian, Socinian). Both on the academic level and on the ecclesiastical level, the Synopsis responds to challenges coming from the immediate context of the early seventeenth century. The disputations of this first volume cover topics such as Scripture, doctrine of God, Trinity, creation, sin, Law and Gospel. Volume One was published in 2014, Volume Two came out in 2016. Volume Three, the final volume, is expected late 2019.